The Influence of Long Working Hours, Occupational Stress, and Well-Being on Depression Among Couriers in Zhejiang, China - Hong, Yu; Zhang, Yixin; Xue, Panqi; Fang, Xinglin; Zhou, Lifang; Wei, Fang; Lou, Xiaoming; Zou, Hua (Frontiers in Psychology, 2022)
Objective This study aimed to examine the association between long working hours, occupational stress, depression and well-being, and to explore the intermediary effect of occupational stress and well-being between working hours and depression among couriers in Zhejiang, China. Methods The study used a cluster random sampling method to select 1200 couriers from mainstream express companies in Zhejiang, China. The data were collected and analyzed using the Core Occupational Stress Scale (COSS) to measure occupational stress, the Patient Health Questionnaire-9 (PHQ-9) scale to evaluate depression, and the World Health Organization five-item Well-Being Index (WHO-5) scale to assess well-being. Structural equation modeling (SEM) was used to test the hypothesized relationship among the variables. Results: The phenomenon of long working hours (89.5%) was quite common among couriers in Zhejiang, China. Working hours had a direct positive effect on depression (β = 0.008, p < 0.001) and on occupational stress (β = 0.009, p < 0.001), and working hours had a negative effect on well-being (β = -0.013, p < 0.001). Occupational stress had a direct positive effect on depression (β = 0.272, p < 0.001). Working hours had an indirect effect on depression through the mediating effect of occupational stress. Conclusion Long working hours, occupational stress were predictors of depression. Working hours had a significant indirect effect on depression via occupational stress. The result of this study showed that decreasing working hours, reducing occupational stress would be effective for couriers to prevent depression. However, more studies are needed to verify the relationship between working hours and depression.